(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: Despite different research studies available advocating various methods of treatment for Pilonidal sinus, recurrence rate and complications are marked. The aim of our study was to evaluate the efficacy of pilondal sinus excision with off midline closure over a suction drain and establish it as a standard treatment protocol. Methods: This prospective study was conducted over a period of six years from March 2005 to April 2011 in Kohat, KPK, Pakistan. A total of 125 patients were included in the study. All the patients were male between 25 to 40 year of age and had chronic pilonidal sinus diagnosed on history and physical examination alone. Extensive shaving of back hair from nape of neck to natal cleft pre- and post operatively at regular intervals for six months was performed. Excision of the chronic pilonidal sinus along with all tracks and recesses with off midline closure over suction drain was done under general anesthesia. Results: Full primary healing was obtained in 112 (89.6%) patients, only 4 (3.2%) patients had recurrence. Wound infection occurred in 9 (7.2%) patients. But all these complications healed. The average stay in hospital was 3 days. Follow up period was 1 year. Conclusion: Off midline closure over the drain is a superior surgical technique to treat pilonidal sinus. It helps in early recovery and discharge from hospital and has minimal recurrence rate.